Joint-specific power production during submaximal and maximal cycling - Elmer, S.; Barratt, P.; Korff, T.; Martin, T. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Cycle ergometry is commonly used to quantify muscular work and power, and to elicit perturbations to metabolic homeostasis for a broad range of physiological investigations. Separate authors have reported that knee extension dominates power production during submaximal cycling (SUBcyc; Ericson, 1988) and hip extension is the dominate action during maximal cycling (MAXcyc, Martin & Brown, 2009). Changes in joint-specific powers across broad ranges of net cycling powers within one group of cyclists have not been reported. Our purpose was to determine the extent to which ankle, knee, and hip joint actions produced power across a range of net cycling powers. Based on previous reports we hypothesized that relative contributions of knee extension power would decrease and relative knee flexion and hip extension powers would increase as net cycling power increased